HUBUNGAN POWER OTOT LENGAN DAN KOORDINASI MATA-TANGAN DENGAN HASIL SERVIS PANJANG DALAM PERMAIAN BULU TANGKIS PADA SISWA EXTRAKURIKULER SMA NEGERI 2 OKU - Daryono . (Universitas Pendidikan Ganesha, 2018)
The purpose of this study was to determine the relationship between muscle strength and eye-hand with the results in badminton games on extracurricular students of OKU 2 State Senior High School. The research method used is a correlational method which aims to determine the relationship between variables. The population in this study were 20 students who participated in badminton extracurricular activities at SMA Negeri 2 OKU, while the total sampling sample of this Research City had a sample of 20 students. The test instruments used were two-handed ball tests, ball catching tests and long service tests. Data analysis techniques used are moment and double product modifications.The results of the study prove that there is a relationship between strength and unit, which is proven by 0.716 based on interpretation interpretation tables that have very strong relationships. There is a relationship between responsibility and long service, as evidenced by as much as 0.512 based on the interpretation table interpretation of medium expression. There are strength and mental relationships that work together with long service, as evidenced by the coefficient of a large number of 0.736 based on the interpretation interpretation table must have a very strong